(untitled) - Gregorietti, Guido (London, 1969)
Illustrated with 400 pictures, over half of them in colour, this book covers the whole range of jewelry through the ages. It includes not only the history of jewelry in Europe, but also India, Africa, Pre-Columbia America and China
Keywords: Jewelry,Đồ trang sức; History